1981
DOI: 10.1002/j.1552-4604.1981.tb02610.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Intramuscular Levonantradol and Placebo in Acute Postoperative Pain

Abstract: Double‐blind administration of a single intramuscular dose of 1.5, 2.0, 2.5, or 3.0 mg levonantradol or placebo to 56 patients with moderate to severe postoperative or trauma pain showed significant analgesic effects of each dose of levonantradol as compared to placebo (P < 0.05). However, no significant dose response was observed. Compared to 2/16 patients on placebo, 23/40 patients (57 per cent) on levonantradol reported one or more side effect. Drowsiness was most frequent. Dry mouth, dizziness, “weird drea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
95
0
2

Year Published

1981
1981
2007
2007

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(108 citation statements)
references
References 4 publications
2
95
0
2
Order By: Relevance
“…Significant pain relief was obtained with levonantradol, but commonly associated with drowsiness. 3 In 2002, Greenwald et al reported the acute antinociceptive properties of inhaled cannabis in recreational drug users. 5 Only five male volunteers completed the study which consisted of three test sessions during which they smoked cigarettes containing 0% (placebo) and 3.55% THC (active).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Significant pain relief was obtained with levonantradol, but commonly associated with drowsiness. 3 In 2002, Greenwald et al reported the acute antinociceptive properties of inhaled cannabis in recreational drug users. 5 Only five male volunteers completed the study which consisted of three test sessions during which they smoked cigarettes containing 0% (placebo) and 3.55% THC (active).…”
Section: Discussionmentioning
confidence: 99%
“…Despite these challenges, we were able to recruit similar numbers of subjects compared to other studies evaluating cannabinoids for postoperative analgesia. 3,7 Furthermore, in these studies, patients received only one dose of study medication compared to three doses in the present study. A practical concern is the use of oral medications during the early postoperative period which may be associated with poor patient tolerance.…”
Section: Limitationsmentioning
confidence: 97%
“…In brief, there were contradictory findings in human studies on pain, with some research suggesting that THC relieved cancer pain about as well as 60 mg of codeine [56,57] and that levonantrodol, a synthetic THC-like cannabinoid was effective in post-operative and trauma pain [58]. On the other hand, Raft et al [59] found no effect of THC on the pain of tooth extraction, and Clark et al [60] found some suggestion that moderate to high doses of THC actually produced hyperalgesia.…”
Section: Results Of Earlier Research With Cannabis Thc and Its Syntmentioning
confidence: 99%
“…It has been used in clinical trials to palliate postoperative pain or pain due to trauma and has shown more analgesic efficacy than placebo [70]. Levonantradol causes adverse effects more often than THC in many patients, but none of them is considered serious.…”
Section: Therapeutic Uses Of Cannabinoids In Pain Episodesmentioning
confidence: 99%